The perception of undergraduates on the use of GramCHQ (Gram-Checked) for online distance learning (ODL) during the COVID-19 pandemic / Kimberley Lau Yih Long, Christine Jacqueline Runggol and Jacqueline Susan Rijeng - Lau, Kimberley Yih Long; Runggol, Christine Jacqueline; Rijeng, acqueline Susan (Universiti Teknologi MARA, 2022)
The COVID-19 pandemic has transformed our education system whereby the largest online movement in the history of education was witnessed and the way lessons were delivered was reshaped. The use of Grammar teaching tools from traditional white boards to electronic screens is worth investigating, especially from the viewpoint of first year Diploma undergraduates as they transitioned from secondary education to tertiary education. This paper presents the acceptance of using GramCHQ (Gram-Checked), a grammar teaching tool designed for Integrated Language Skills 1 (ELC121) ODL lessons. The objectives of the study were to identify the perceptions of undergraduates towards lessons conducted using GramCHQ and elicit their feedback on the effectiveness of GramCHQ lessons. A total of 97 undergraduates from four different Diploma programs participated in this study. They were guided on how to use GramCHQ before being asked to experience the lesson themselves. After the lesson, they were asked to fill in e-questionnaires designed in Google Form. The findings from the survey revealed that participants reacted positively to GramCHQ with high learner's self-perceptions of GramChQ usefulness (m=4.12). In addition, good perceptions (m>3.80) were obtained in terms of GramChQ's interest, relevance, presentation, technology, enjoyment, memorisation and future demand. Furthermore, GramCHQ is an effective medium for Online Distance Learning as its low bandwidth caters to a larger population as well as engaging its learners' interests with its interactive game-based learning approach. Findings from this study provide a basis for educators to plan effective online teaching strategies for digital classrooms.